Viral bronchiolitis in young infants: new perspectives for management and treatment - Mauricio T. Caballero; Fernando P. Polack; Renato T. Stein
Abstract Objective: The aim of this review was to address advances in management and treatment of acute viral bronchiolitis in infants. Sources: A systematic review search was made including all articles published in English between 2010 and 2017, and available in the electronic databases PubMed and Cochrane Central Register of Controlled Trials (CENTRAL) and specialized register of the Acute Respiratory Infections Group (Cochrane review group). The following MESH terms in English were included, using different Boolean operators for the search strategy: "bronchiolitis, viral," "diagnosis," "epidemiology," "etiology," "therapy," "virology," "prevention and control," "respiratory syncytial virus, human." Additional filters were used. Summary of findings: Few effective interventions are recommended for the management of RSV bronchiolitis in young infants. The main goal is to ensure an adequate oxygen supplementation and fluid balance whenever deemed necessary. Hypertonic saline nebulization is helpful only for hospitalized infants. Numerous antiviral drugs and specific vaccines for RSV are under evaluation and foretell advances in disease management in the near future. Conclusion: A number of promising new technologies are advancing in the field. Until new interventions became feasible, early detection and modification of preventable risk factors is essential to improve outcomes.